2019
DOI: 10.3390/cells8060545
|View full text |Cite
|
Sign up to set email alerts
|

Building Blood Vessels—One Rho GTPase at a Time

Abstract: Blood vessels are required for the survival of any organism larger than the oxygen diffusion limit. Blood vessel formation is a tightly regulated event and vessel growth or changes in permeability are linked to a number of diseases. Elucidating the cell biology of endothelial cells (ECs), which are the building blocks of blood vessels, is thus critical to our understanding of vascular biology and to the development of vascular-targeted disease treatments. Small GTPases of the Rho GTPase family are known to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 120 publications
0
20
0
Order By: Relevance
“…This allows new blood vessels to form within the tumor, alleviates nutrient deficiency and promotes metastasis. As Rho GTPases function within specific vascular cell types, and some Rho GTPases are also expressed in diseased vessels [ 67 ], recent studies have shown that Rho GTPases are important for angiogenesis.…”
Section: Rho Gtpases In Primary Tumor Growth and Angiogenesismentioning
confidence: 99%
“…This allows new blood vessels to form within the tumor, alleviates nutrient deficiency and promotes metastasis. As Rho GTPases function within specific vascular cell types, and some Rho GTPases are also expressed in diseased vessels [ 67 ], recent studies have shown that Rho GTPases are important for angiogenesis.…”
Section: Rho Gtpases In Primary Tumor Growth and Angiogenesismentioning
confidence: 99%
“…Upon activation, αvβ3 integrin initiates a signaling cascade in which an important role is played by rat sarcoma (Ras)-related C3 botulinum toxin substrate 1 (Rac1) that belongs to the Rho proteins, which are a dynamic group of GTPases participating in a multitude of cellular activities and functions. From their effects on the expression of angiogenic factors to their role in the integrin signaling pathways and endothelial cell morphogenesis, Rho proteins prove to be an important part of the angiogenesis machinery [74]. Little is known about uPAR interaction with αvβ3 integrin although there are some indications that αvβ3 integrin is implicated in regulatory functions mediated by the uPAR system.…”
Section: Upar-co-receptor Interactionmentioning
confidence: 99%
“…The role of HSP27 phosphorylation in the regulation of endothelial permeability remains controversial [ 25 , 26 , 27 , 28 , 29 ]. In addition, small Rho GTPases are crucial orchestrators of actin organization and contractility [ 23 , 30 ]. RhoA promotes stress fibers contraction, while Rac1 reinforces IEJs’ anchorage to the plasma membrane by promoting the development of a cortical actin network [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%